Strategi Coping Santri Dalam Menghadapi Standar Kelulusan Di Pondok Pesantren - Segoro, Tirtha; , Dr. Taufik, M.Si (2015)
The aims of this research are to understand and describe the student perception towards graduation standard, the coping strategy of student and the factors that affect coping strategy of student in handling a graduation standard in Islamic boarding school. The informan's characteristics are student of PPMI Assalaam and PPA Al-Muayyad, Class of XII senior high school, 16-18 years old, student who has a high grade and student who has difficulty in handling a graduation standard. The informants were six people and the used method is an interview. The results of research: 1) Student perception towards graduation standard is agree especially in school's graduation requirements for caring a positive influence for student and disagree especially UN (National Exam), because of a burdensome and a lot of injustices; 2) Coping strategy that been used by student is emotion-focused coping, covering get permission to go out the boarding school, have a relationship with the opposite sex, open an online-shop, joke around with roommates, read a story book, cheer them self by singing and washing clothes. But, the most effective coping strategy for students is problem-focused coping, covering choose a conducive place, start doing the requirement from the previous year, reading and repeating often, doing a routine consultation with tutors, offset learning (follow the guidance of learning, exercise more often, work and study together with friends), increasing a worship and consistent in running the activities; 3) the factors that affect the coping strategy of student are personal characteristic, self perception, family support, school and social which is in the boarding school, friend is the closest social support. The conclusion of the results of this research is the student uses a problem-focused coping as the most effective coping strategy in handling a graduation standard. Implications hat van be given is need a support from family, school and friends for student in handling a graduation standard.